Interpreting the self : autobiography in the Arabic literary tradition - Reynolds, Dwight Fletcher, 1956-; Brustad, Kristen (University of California Press, 2001)
Autobiography is a literary genre which Western scholarship has ascribed mostly to Europe and the West. Countering this assessment and presenting many little-known texts, this comprehensive work demonstrates the existence of a flourishing tradition in Arabic autobiography.